Avaliação do desempenho ambiental em termos de consumo hídrico, energético e geração de resíduos em canteiros de obras de edificações - Albertini, Felipe Mattos (Universidade do Vale do Rio dos Sinos, 2019)
The contemporary scenario calls for better environmental practices, both globally and locally, where sustainable development has been a common goal. For these reasons, environmental liability is imposed on companies, including construction, because the industry is known for its high expenditure on the environment due to the high size it occupies in the market. Therefore, the present study questions in relation to the notable inefficiency during the stage of construction of buildings, regarding environmental aspects such as waste generation, water and energy consumption, translated as environmental performance. In order to answer this question, it was used the Data Envelopment Analysis (DEA), which indicates a technical efficiency index of each construction site, considering input and output data in order to compare each result. Allied to the use of censored regression (tobit) that had as purpose to investigate the influence of qualitative aspects in the calculated efficiency. As results, an average efficiency of 83.5% was calculated, and 5 of the 16 constructions works observed were 100% efficient. As for the description of the observed facts, the following performance indicators are pointed out: 10.5 kWh / m2 in energy consumption, 0.37m3 / m2 for water consumption and in the generation of waste, a total of 0.15 m3 / m2 of waste. Finally, the analysis of the censored regression showed that the constructive pattern corroborated in the decrease of the environmental performance index, and in counterpart aspects of the productive system and management during the construction work, they are relevant to increase the efficiency of the evaluated environmental aspects.
Keywords: Sustentabilidade na Construção; Consumo de Água e Energia; Resíduos de Construção e Demolição; Análise Envoltória de Dados; Regressão Tobit; Sustainability in Construction; Water and Energy Consumption; Construction and Demolition Waste; Data Envelopment Analysis; Tobit Regression; ACCNPQ::Engenharias::Engenharia Civil